Inheritance Distribution Before Death: A Study in Teluk Kasai, Indonesia - Nisa, Nurul Aulia; Fitri, Devianti (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
In terms of legal practice, the division of inheritance must take place while the heir is still living, and it is more common for the practice of jointly splitting inheritance between a husband and wife to take the shape of income and inheritance after the heir passes away. As everyone is aware, inheritance law governs how the estate of the deceased is inherited and how it affects the heirs. This study discusses the inheritance distribution system in the community of Kampung Teluk Kasai, Kenagarian Koto Nan Duo, Batang Kapas District, Pesisir selatan Regency. This study used a qualitative research methodology. In principle, the distribution of inheritance according to Islamic Law occurs after the heirs pass away.